PENILAIAN KINERJA KANTOR DINAS PEMBERDAYAAN MASYARAKAT DAN DESA DI KABUPATEN KARANGANYAR JAWA TENGAH TAHUN 2020 - Jalu Prasetya Aji; Qomaruddin Qomaruddin (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The main function of the government, especially the Community and Village Empowerment Office, is to serve the community so that it is necessary to continuously work to improve the quality of services. One of the efforts that must be made in improving public services is to assessment performance. The measure of the success of service delivery is determined by the performance of the service itself as measured by various indicators including the level of satisfaction of service recipients. This study aims to measure the performance of the Community and Village Government Empowerment Office in the Karanganyar District Community and Village Empowerment Office. Method: The design of this study uses a quantitative descriptive study and uses a cross-sectional study approach. The location of this research was carried out at the Karanganyar Regency Community and Village Empowerment Service. The sample in this study was the village apparatus totaling 62 people from 162 villages in Karanganyar Regency. The sampling technique used was the accidental sampling technique. The research instrument used interview guides and questionnaires. Quantitative data analysis uses frequency distribution based on aspect weights. Results: The performance of the Community and Village Empowerment Agency in Karanganyar Regency was in a sufficient category but with notes. it is better to improve the quality of public services by paying attention to good service standards by its aspects.